Ketimpangan Wilayah Perkotaan dan Dampaknya Terhadap Lingkungan: Studi Kasus Kota Mataram dan Kota Bima, Nusa Tenggara Barat - Nur Alfatiha; Wira Adytia; Reno Febrian (Lembaga Publikasi Ilmiah Nusantara, 2025)
Urban development inequality is a critical issue in achieving sustainable development, particularly in West Nusa Tenggara (NTB), Indonesia. This study compares Mataram City, the provincial capital, and Bima City, a secondary city, using a quantitative-descriptive approach based on secondary data from the Central Statistics Agency (BPS) and literature review. Analyses employed Klassen Typology, Human Development Index (HDI), and Williamson Index. Results show significant disparities: Mataram’s per capita GRDP is IDR 54.38 million with an HDI of 81.15, while Bima’s figures are IDR 32.61 million and HDI 75.80. The Williamson Index (0.44) indicates considerable inequality, influencing environmental quality. Mataram faces urbanization-induced air pollution and green space reduction, whereas Bima suffers from sanitation issues, flooding, and poor waste management. Addressing these disparities requires integrating economic policies with ecosystem-based spatial planning and strengthening environmental management in secondary cities.